Polymer Nanocomposite Coatings for CO2 Pipeline Corrosion Control: A Comprehensive Review - Oloto, Jerome; Kapfudzaruwa, Simbarashe; Muthu, S.D. Jacob (Journal of Research Updates in Polymer Science, 2025)
Carbon dioxide (CO2) is the most significant greenhouse gas, accounting for 77% of global warming and is produced by the combustion of fossil fuels in industries. Carbon capture, storage and utilization (CCUS) is a possible pathway in achieving the emission reduction target set by the Canadian government in 2050. The transportation of the captured CO2 to storage is a critical factor in the CCUS process, which is frequently hindered by corrosion. The impurities in CO2 lead to corrosion risks, which are generally addressed using inhibitors, corrosion-resistant alloys, and polymer coatings in the oil and gas sector. However, CO2 corrosion is more complex than CO2 sweet corrosion. It is difficult to obtain a single inhibitor capable of mitigating CO2 corrosion in pipelines, and corrosion-resistant alloys are too expensive to be used throughout all sections of the pipeline. Polymers are employed as coatings. For gaseous and supercritical CO2, which leads to defects in the coatings, such as blisters and porosity. As a result, researchers have focused on using nanocomposite coatings to control CO2 corrosion. This review paper focused on the interactions of CO2 with impurities on polymer and polymer nanocomposites. In particular, the most commonly used clay and graphene polymer nanocomposites coatings and their interactions with CO2 were discussed. Further, the transport properties of CO2 through polymers and polymer nanocomposites and the interaction mechanism were analyzed. The paper concludes with the processing methods used for the polymer and polymer nanocomposite coatings.